A Traditional Mu'tazilite Qur'ān Commentary : The Kashshāf of Jār Allāh al-Zamakhsharī (d.538/1144) - Lane, Andrew, (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
This book deals with the life and work of Jār Allāh al-Zamakhsharī (d. 538/144). The greater part of it, however, is devoted to an examination of his Qurʾān commentary, al-Kashshāf. The book is divided into five chapters, supplemented by nine appendices. After a chapter on the author's life and writings (an annotated list of which is given in an appendix), there follow four chapters that focus on the Kashshāf itself. These deal with the history of the text, its structure and method, the traditions it contains and the sources the author relied on for it. Although both al-Zamakhsharī's name and the title of his commentary are well known, very little is actually known about either the author or the work. This book presents a more complete and nuanced picture of each.